NUTRITIONAL ANALYSIS AND SENSORY EVALUATION OF READY-TO-USE THERAPEUTIC FOOD FORMULATED FROM LOCALLY SOURCED INGREDIENTS IN BORNO STATE, NIGERIA, COMPARED TO UNICEF STANDARDS - Ali, Frichan; Nyaze, Sharon; Magaji, Sa'eedu; Anyanwu, Gabriel; Adoga, Godwin (FUDMA JOURNAL OF SCIENCES, 2025)
Severe acute malnutrition (SAM) remains a major public health concern in Nigeria, particularly in the northeastern region where child mortality rates are disproportionately high. Ready-to-Use Therapeutic Foods (RUTFs) have proven effective in managing SAM; however, dependence on imported products limits access due to high costs and supply instability. This study formulated and evaluated two locally produced RUTFs (MSD-01 and MSD-02) using millet, soybean, groundnut, date palm, catfish, and peanut oil sourced from Borno State. Analyses were conducted following AOAC (2010) protocols for proximate composition, vitamins, minerals, fibre, fatty acids, and anti-nutritional factors, while sensory evaluation employed a five-point hedonic scale. Both formulations were energy-dense (565–572 kcal 100 g⁻¹), exceeding the UNICEF specification of 520–550 kcal 100 g⁻¹ by approximately 10%. Fat levels (39–41 g 100 g⁻¹) were elevated, suggesting potential protein–energy imbalance, while protein contents (10–11 g 100 g⁻¹) were critically below the 12.8–16.2 g 100 g⁻¹ therapeutic range. Micronutrient analysis revealed adequate vitamin A but severe deficiencies in vitamins C and E, niacin, zinc, iron, calcium, and magnesium. Crude fibre (≈ 2.4 g 100 g⁻¹) and fatty acid profiles were within acceptable limits. Anti-nutritional compounds such as phytates (< 10 mg 100 g⁻¹) and tannins (< 110 mg 100 g⁻¹) were below inhibitory thresholds. Sensory evaluation indicated moderate acceptability (mean scores ≈ 7/9), with no significant differences (p > 0.05) between formulations. The findings suggest that locally sourced RUTFs are feasible and culturally acceptable but require protein enrichment and micronutrient fortification to meet UNICEF/WHO standards.
Keywords: Ready-to-Use Therapeutic Food (RUTF); malnutrition; micronutrient deficiencies; sensory evaluation; fortification